Penguatan Kesadaran Pengunjung melalui Edukasi Sense of Place pada Ruang Publik Islami Plaza Masjid Raya Baiturrahman Banda Aceh - Mirza Fuady; Nasrullah Ridwan; Buraida Buraida; Rizal Munadi; Al Asy’ari Al Asy’ari; M Andrian Kevin; M Rafi Farrel; Allya Triaputri (Universitas Syiah Kuala, 2026)
This community service program aimed to improve visitors’ awareness and understanding of ethical behavior in Islamic public spaces through a sense of place-based educational approach at the Plaza of Baiturrahman Grand Mosque, Banda Aceh. The program was conducted in response to several inappropriate visitor behaviors identified in the mosque plaza area, including littering, smoking in restricted areas, and activities that reduced the comfort and sanctity of the mosque environment. The target participants consisted of plaza visitors, religious tourists, and mosque management personnel. The implementation applied participatory and educational methods through field observation, direct socialization, interactive discussions, and evaluation with mosque managers. Educational activities emphasized the importance of maintaining cleanliness, orderliness, comfort, and respect for Islamic public spaces by strengthening visitors’ understanding of the symbolic meaning and religious value of the mosque plaza. In addition, the program highlighted the importance of environmental comfort and supporting facilities in enhancing visitor experience during activities in the mosque area. The program applied persuasive communication and contextual educational strategies to encourage collective responsibility toward the public environment. The results indicated an improvement in visitors’ awareness regarding ethical behavior, environmental cleanliness, and respect for religious public spaces. The findings demonstrate that a sense of place-based educational approach can support the development of sustainable, orderly, comfortable, and value-oriented Islamic public spaces.